Evalutaion of thunderstrom hazards within Peninsular Malaysia using geographical information system (GIS) - Chin, Steny Loong (2015)
Malaysia is one of the highest occurence of thunderstorm activity in the world. Situated close to the equator, the warm and humid tropical conditions are highly favourable for the development of thunderstorm. This related to its characteristics itself such as gust factor. Gust factor defme as the ratio between a peak wind gust and mean wind speed over a period of time. For that reason, this study is conducted to investigate the characteristic of thunderstorm in Peninsular Malaysia.There are 12 meteorological stations in Peninsular Malaysia were used. Geographical Information System software were used in order to examine the thunderstorm event in Peninsular Malaysia. From the result it is shown thunderstorm were periodically repeated anually. Higher gust factor was favorably indentified during the Inter monsoon season. From the observation, the damage may frequently occured at higher gust factor area. It can be conclude that higher gust factor will increase the risk of particular area. This application will guide us to get the information about the location and to identify thunderstorm hazard potential.